Afebrile Neuroleptic Malignant Syndrome associated with Fluphenazine decanoate: A case report - Marzieh Assareh; Laleh Koohi Habibi (Iranian Journal of Psychiatry, 2010)
"nNeuroleptic Malignant Syndrome (NMS) is unusual but could be a lethal reaction associated with neuroleptic drugs. It occurs in almost 0.07-2.2% of patients under treatment with neuroleptics. There are some medical treatments that may also be helpful for its treatment, including dopamine agonists, muscle relaxants, and electroconvulsive therapy (ECT). We present this case to alert the clinicians to the potential for inducing afebrile NMS. Our case is a 41-year-old man with a history of schizophrenia showing signs and symptoms in accordance with NMS, 2 weeks after receiving one dose of 12.5 mg fluphenazine decanoate, abruptly following the 3rdsession of ECT. The patient presented with decreased level of consciousness, muscular rigidity, waxy flexibility, mutism ,generalized tremor, sever diaphoresis and tachycardia which progressed during the previous 24 h. Laboratory data indicated primarily leukocytosis, an increasing level of creatinine phosphokinase and hypokalemia during the next 72h. In patients receiving antipsychotics, any feature of NMS should carefully be evaluated whether it is usual or unusual particularly in patients receiving long acting neuroleptics.